The education system development strategy: How to accelerate the improvement of academic qualification for the Indonesian national army? - Wuryanto, Agus; Komariah, Aan; Yuniarsih, Tjutju; Suryana, Asep (Universitas Jambi, Indonesia, 2025)
This research proposes strategic recommendations to address the issues arising in improving the academic qualifications of the Indonesian National Army - in Indonesia. The scoping review method is used to see how other countries handle similar issues. The Scopus database retrieved relevant articles published from 2015 to 2025 with the help of Harzing Publish or Perish. Initially, 199 articles were obtained. Three selection stages based on inclusion criteria determined that 14 articles were selected for an in-depth review. The results are 1) 5 fundamental aspects and eight methodological aspects related to developing military education systems to enhance military personnel’s competencies and academic qualifications in various countries. 2) 4 recommendations promoted: 1) Creation of Prior Learning Recognition, 2) Empowerment of Civilian Roles in Military Academy Curriculum, 3) Military Education Based on International Collaboration, and 4) Utilization of Renewable Technology in Military Education. The results of this research are highly valuable, as they can serve as strategic recommendations for developing the military education system in Indonesia.